Mapati and the Encounter of Islam and Culture in the Pregnancy Traditions of the Palang Community, Tuban - Meilani; Revia Eka Dian Aprilia; Novita Sari; Nurul Hakim (Aimmah: Social Sciences Journal, 2026)
This study aims to describe the implementation of the mapati tradition in pregnancy within the Palang, Tuban community, identify the cultural elements and Islamic values embedded in it, analyze the form of interaction (acculturation) between Islam and local culture, and reveal the meaning of this tradition for the community. This research employs a descriptive qualitative approach using interviews with a local religious figure, supported by literature review. The findings show that the mapati tradition is carried out as a thanksgiving ritual at four months of pregnancy, involving Qur’anic recitations, diba’an, and collective prayers. The tradition reflects a blend of local cultural practices such as slametan and food sharing with Islamic values including gratitude, supplication, and hope for the well-being of the unborn child. The encounter between Islam and culture is evident in the integration of religious practices into local traditions. The mapati tradition is meaningful as an expression of gratitude, a prayer for safety, and a medium for strengthening social bonds. Therefore, it remains relevant as a form of harmony between Islamic teachings and local culture.